(untitled) (Global Journal of Human-Social Science, 2016)
There are two basic purposes to conduct this study in D.G Khan area i.e. to evaluate the methodology for teaching English language at secondary level in government school and to take the perspective from the students about the present teaching methodology of their teachers. For this purpose, we have selected six out of nine government secondary schools of both girls and boys three from each. We have used simple random sampling technique for the collection of data and used inferential, descriptive and one tailed test for the analysis of the data. Total 300 students of both girls and boys Schools are included in the sample and thirty teachers at secondary level are included. Two questionnaires: one for teachers and the other for students were developed for data collection. These questionnaires were distributed personally along with the permission letter so that we do not face any kind of difficulty for collecting data. Results were analyzed SPSS software. The finding of our study is that GTM is liked by the students of D.G Khan and 80 percent of teachers are using in the classes, which means this method is more convenient and popular among the teachers and the students.